An Atypical Cause of Atypical Chest Pain - Ahmad Zaheen; Reed A Siemieniuk; Patrick Gudgeon (Canadian Journal of Infectious Diseases and Medical Microbiology)
The present report describes a case involving a 57-year-old HIV-positive man who presented with acute retrosternal chest pain accompanied by 24 h of fever. Septic arthritis of the manubriosternal joint was diagnosed based on magnetic resonance imaging findings in addition to Staphylococcus aureus bacteremia. To the authors’ knowledge, the present case is only the 12th reported case of manubriosternal septic arthritis, and the first in an HIV-positive patient. Early diagnosis and treatment can circumvent the need for surgical intervention. Based on the present case report and review of the literature, the authors summarize the epidemiology, appropriate imaging and suggestions for antibiotic therapy for this rare presentation.